2013
DOI: 10.1128/aem.03182-12
|View full text |Cite
|
Sign up to set email alerts
|

Syringyl-Rich Lignin Renders Poplars More Resistant to Degradation by Wood Decay Fungi

Abstract: bIn order to elucidate the effects of lignin composition on the resistance of wood to degradation by decay fungi, wood specimens from two transgenic poplar lines expressing an Arabidopsis gene encoding ferulate 5-hydroxylase (F5H) driven by the cinnimate-4-hydroxylase promoter (C4H::F5H) that increased syringyl/guaiacyl (S/G) monolignol ratios relative to those in the untransformed control wood were incubated with six different wood decay fungi. Alterations in wood weight and chemical composition were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 67 publications
5
60
0
5
Order By: Relevance
“…Cultures were incubated for 5 days on a rotary shaker (150 rpm) at 37°C. Carbohydrate and lignin composition levels of wood samples have been reported previously (21). Notably, line 64, line 82, and parental line P717 had similar overall lignin contents but feature approximately 94 mol%, 85 mol%, and 65 mol% syringyl units, respectively.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Cultures were incubated for 5 days on a rotary shaker (150 rpm) at 37°C. Carbohydrate and lignin composition levels of wood samples have been reported previously (21). Notably, line 64, line 82, and parental line P717 had similar overall lignin contents but feature approximately 94 mol%, 85 mol%, and 65 mol% syringyl units, respectively.…”
Section: Methodsmentioning
confidence: 81%
“…In recent years, lignin composition in poplar has been modified by gene misregulation, and, in one case, altered lignin improved the efficiency of saccharification and fermentation to ethanol (20). The enzymatic mechanisms underlying lignin degradation remain uncertain, but recent analysis suggests that transgenic poplar with increased ratios of syringyl to guaiacyl lignin monomers are relatively more resistant to fungal attack (21).…”
mentioning
confidence: 99%
“…The chemical composition of extractives depends directly on the wood species, and important variability exists among the ones mentioned above, leading to important variations in their content, chemical composition, and biological properties (55). A recent study showed that transgenic poplar lines enriched in syringyl lignin are more resistant to fungal degradation, suggesting a toxic effect of these subunits (56).…”
Section: Transcriptomic Analysis (I) Overview Of Gene Expressionmentioning
confidence: 99%
“…Previous studies have shown that during the initial stages of fungal degradation, the carbohydrates most modified were sugars derived from the primary walls and middle lamella (galactose and arabinose). These are often recognized as the building blocks of hemicelluloses and/or arabinogalactan proteins in the primary wall (Skyba et al 2013).…”
Section: Resultsmentioning
confidence: 99%